Insights into Feruloylated Oligosaccharide Impact on Gel Properties of Oxidized Myofibrillar Proteins Based on the Changes in Their Spatial Structure - Jingchao Yu; Shouwei Wang; Chengfeng Sun; Bing Zhao (Foods, 2023)
Polyphenolic compounds can protect against myofibrillar protein (MP) oxidation in meat products. In this study, the inhibitory effect of feruloyl oligosaccharides (FOs) on MP oxidation was investigated, and the gel properties of MPs were further studied. The results showed that 50–100 μmol/g protein of FOs could effectively inhibit damage to amino acid side chains by reducing carbonyl contents by 60.5% and increasing sulfhydryl and free amine contents by 89.5% and 66%, which may protect the secondary and tertiary structures of MPs. Additionally, FOs at 50 μmol/g protein had better effects on the crosslinking of MPs, leading to effective improvements in the gel properties, which can be seen in the rheology properties, scanning electron microscope (SEM) photographs, and the distribution of water in the MP gel. On the contrary, 150–200 μmol/g protein of FOs showed peroxidative effects on oxidatively stressed MPs, which were detrimental to MPs and contributed to their denaturation in the electrophoresis analysis and irregular aggregation in the SEM analysis. The concentration-dependent effects of FOs depended on MP-FOs interactions, indicating that an appropriate concentration of FOs has the potential to protect MPs from oxidation and enhance the gelation ability of pork meat during processing.